Hubungan Aktivitas Fisik Dengan Tekanan Darah Pada Penderita Hipertensi Di Rumah Sakit Muhammadiyah Palembang - Siti Maskanah; Suratun Suratun; Sukron Sukron; Yulius Tiranda (Jurnal Keperawatan Muhammadiyah, 2019)
Objective: To find out the relationship between the physical activity and blood pressure hypertensive patients of Muhammadiyah Hospital of Palembang. Methode: Cross sectional method was used with the number of sample of 67 hypertensive patients taken by using purposive sampling technique: The Fisher Exact test was used to analyze the relationship between physical activity and blood pressure.Results: The result showed that most of the activities carrie d out were moderate activities (67,2%). The result pf the analysis showed that there was a significant relationship between physical activity and systole and diastolic blood pressure with each p value of 0,003, OR: 6,458 and p value 0, 013, OR: 144.  Conclusion: There was a significant relationship between phsical activity and blood pressure. It is expected that health workers be able to play an active role and involve families in optimizing phsical activity for patient with hypertension.